Impact of uteroplacental insufficiency on ovarian follicular pool in the rat - Valentina Pampanini; Kirsi Jahnukainen; Lena Sahlin; Daniela Germani; Antonella Puglianiello; Stefano Cianfarani; Olle Söder (BMC, 2019)
Abstract Background A low oxygen supply to the fetus causes intrauterine growth restriction and can affect gonadal development of the offspring, having a potential impact on fertility. We investigated histology and gene expression in the postnatal rat ovary after fetal hypoxia induced by uterine artery ligation. Methods Sprague-Dawley rats underwent uterine artery ligation at day 19 of gestation. Offspring were sacrificed at 5, 20 and 40 days post-partum. Follicles were counted and classified in hematoxylin-eosin stained sections. Gene expression of 90 genes was analyzed by TaqMan® Low Density Array. Results A significantly lower number of total and primordial follicles was detected in 20 days post-partum intrauterine growth restricted animals. Follicle density was not different at 40 days post-partum, suggesting that compensatory mechanisms occurred during the pre-pubertal window. Uterine artery ligation modified the expression of 24 genes involved in different cellular functions, among which proliferation, apoptosis and metabolism. Conclusion Ovarian follicle pool was affected by fetal hypoxia in early life, but this effect did not persist in puberty. Genes involved in cellular processes were affected at all ages, potentially implying long-term genetic alterations. Further analyses are needed to elucidate later effects of fetal hypoxia on ovarian function and fertility.